Предмет: Алгебра,
автор: burbin997
Помогите пожалуйста)
Преобразуйте в многочлен:
А)2х(х-3)-3х(х+5)
Б) (а+7)(а-1)+(а-3)2
В)4у(3у+6)-(3у-5)(3у+5)
Ответы
Автор ответа:
0
а)2x(x-3)-3x(x+5)=2x2-6x-3x2-15x=-x2-21x
б)(а+7)(а-1)+(а-3)=a2+a+7a+7+a-3=a2-5a+4
Автор ответа:
0
а)2х(х-3)-3х(х+5)=(2х^2-6х)-(3х-15х)=2х^2-6х-3х^2+15х=-х^2+9х;
б)(а+7)(а-1)+(а-3)2=(а^2-а+7а-7)+(2а-6)=а^2-а+7а-7+2а-6=а^2+8а-13;
в)4у(3у+6)-(3у-5)(3у+5)=12у^2+24у-9у^2-15у+15у+25=3у^2+24у+25;
Объяснение:
у^2= у в квадрате
б)(а+7)(а-1)+(а-3)2=(а^2-а+7а-7)+(2а-6)=а^2-а+7а-7+2а-6=а^2+8а-13;
в)4у(3у+6)-(3у-5)(3у+5)=12у^2+24у-9у^2-15у+15у+25=3у^2+24у+25;
Объяснение:
у^2= у в квадрате
Похожие вопросы
Предмет: Русский язык,
автор: igortym777
Предмет: Технология,
автор: 56790456
Предмет: Українська мова,
автор: ystefaniv04
Предмет: Английский язык,
автор: artem04022012044